(untitled) (Research, Society and Development, 2021)
This work aimed to make a comparative evaluation of the thermal comfort of environments in a mining company in the Northwest of Minas Gerais, where there is a green roof with environments where there is no such roof. It was possible to analyze and observe through research and comparative results obtained from temperatures and relative humidity that act on the thermal comfort of environments in work activities. In this work, measurements were performed in loco with Dataloggers equipment that allowed all the necessary data collection to carry out the comparisons of internal and external temperatures and relative humidity. The results were compared to the literature consulted, which showed satisfactory thermal comfort, but in view of NR17, thermal comfort was not met. Thus, at the end of this work, a suggestion was given to improve thermal comfort in relation to the temperature and relative humidity of the environments in work activities.